2022
DOI: 10.1051/0004-6361/202142555
|View full text |Cite
|
Sign up to set email alerts
|

Type II supernovae from the Carnegie Supernova Project-I

Abstract: Type II supernovae (SNe II) show great photometric and spectroscopic diversity which is attributed to the varied physical characteristics of their progenitor and explosion properties. In this study, the third of a series of papers where we analyse a large sample of SNe II observed by the Carnegie Supernova Project-I, we present correlations between their observed and physical properties. Our analysis shows that explosion energy is the physical property that correlates with the highest number of parameters. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 106 publications
1
14
0
2
Order By: Relevance
“…Observationally, this also implies that the explosion of a star similar to the progenitor of F15.78 would appear much dimmer than a star similar to F15.79. The higher 56 Ni yield and 2.5 times higher explosion energy in F15.79 follows the strong correlation between the explosion energy and the production of 56 Ni seen in observations (see, e.g., Martinez et al 2022). As discussed in Section 2, the 15.79 M ☉ preSN model has higher compactness than the 15.78 M ☉ preSN model, correlating with the higher 56 Ni yields inF15.79, agreement with the finding of Ebinger et al (2019), for neutrino-driven, spherically symmetric explosions, that higher compactness correlates with higher 56 Ni yields.…”
Section: Isotopic Yieldssupporting
confidence: 63%
“…Observationally, this also implies that the explosion of a star similar to the progenitor of F15.78 would appear much dimmer than a star similar to F15.79. The higher 56 Ni yield and 2.5 times higher explosion energy in F15.79 follows the strong correlation between the explosion energy and the production of 56 Ni seen in observations (see, e.g., Martinez et al 2022). As discussed in Section 2, the 15.79 M ☉ preSN model has higher compactness than the 15.78 M ☉ preSN model, correlating with the higher 56 Ni yields inF15.79, agreement with the finding of Ebinger et al (2019), for neutrino-driven, spherically symmetric explosions, that higher compactness correlates with higher 56 Ni yields.…”
Section: Isotopic Yieldssupporting
confidence: 63%
“…See Appendix A for details of the photometry reduction. We also include publicly available photometry from the ATLAS forced photometry server (Tonry et al 2018a;Smith et al 2020) and the Supernova Observations and Simulations group (Martinez et al 2021). Figure 1 shows the light curve of SN 2021yja; the data are available in machinereadable format in the online journal.…”
Section: Follow-up Photometry and Spectroscopymentioning
confidence: 99%
“…One proposed solution to the RSG problem is that the RSGs with initial masses M i M h lose enough of their envelopes through mass loss or interactions with a binary companion to evolve blueward in the HR diagram before exploding (e.g., Ekström et al 2012;Neugent et al 2020), possibly as SESNe. Indeed, such enhanced mass-loss rates are observed in massive RSGs (Humphreys et al 2020), and may also be necessary to explain the observed diversity of SNe II (Martinez et al 2022).…”
Section: Introductionmentioning
confidence: 96%